Assessment of internal exposure to 131I and short-lived radioiodine isotopes and associated uncertainties in the Ukrainian cohort of persons exposed in utero. (17th March 2022) - Masiuk, Sergii; Chepurny, Mykola; Buderatska, Valentyna; Ivanova, Olga; Boiko, Zulfira; Zhadan, Natalia; Hatch, Maureen; Cahoon, Elizabeth K; Zamotayeva, Galyna; Shpak, Victor; Tronko, Mykola; Drozdovitch, Vladimir
Abstract: This study revised the thyroid doses for 2582 Ukrainian in utero cohort members exposed to Chornobyl fallout (the Ukrainian in utero cohort) based on revision of: (i) 131 I thyroid activity measured in the Ukrainian population, (ii) thyroid dosimetry system for entire Ukraine, and (iii) 131 I ground deposition densities in Ukraine. Other major improvements included: (i) assessment of uncertainties in the thyroid doses considering shared and unshared error, and (ii) accounting for intake of short-lived radioisotopes of tellurium and iodine ( 132 Te+ 132 I and 133 I). Intake of 131 I was the major pathway for thyroid exposure, its median contribution to the thyroid dose was 97.4%. The mean prenatal and postnatal thyroid dose from 131 I was 87 mGy (median = 17 mGy), higher than previous deterministic dose of 72 mGy (median = 12 mGy). For 39 individuals (1.5%) the dose exceeded 1.0 Gy, while the highest dose among the cohort members was 2.7 Gy. The geometric standard deviation (GSD) of 1000 individual stochastic doses varied from 1.9 to 5.2 with a mean of 3.1 and a median of 3.2. The lowest uncertainty (mean GSD = 2.3, median GSD = 2.2) was found for the subjects whose mothers were measured for 131 I thyroid activity, while for individuals, whose mothers were not measured, the mean and median GSDs were 3.4. Uncertainties in thyroid doses were driven by shared errors associated with the parameters of the ecological model.